A Validated Reverse-Phase High Performance Liquid Chromatography (RP-HPLC) Method for the Quantification of Gamma- Tocotrienol in Tocotrienol Rich Fractions of Crude Palm Oil - Nair, Rajesh S.; Billa, Nashiru; Morris, Andrew (Current Nutrition & Food Science, 2022)
Background: Palm oil and its constituents have wide applications in food, cosmetics and pharmaceutical industries. The tocotrienol-rich fractions of crude palm oil have drawn greater research interest in recent years due to their potent health benefits. Therefore, reliable and validated analytical methods are essential for the quantification of tocotrienols. Objective: This study aimed to develop a simple and economical RP-HPLC method for the quantification of gamma-tocotrienol in tocotrienol-rich fractions of crude palm oil. Methods: An Agilent HPLC system supplied with a Diode Array detector and an auto-injector system was used for the method development, and the wavelength was set 295 nm. A reversedphase C18 column maintained at 30 °C using a mobile phase composition of methanol: water (95:05) at a flow rate of 1 mL/min was used for the analysis. The developed method was validated according to ICH guidelines. Results and Discussion: A symmetrical peak of gamma-tocotrienol was observed at 8.7 minutes with minimal peak tailing (between 0.76 and 0.78), and an acceptable resolution above 2.0. Excellent linearity was evident with R2 values 0.9996 and 0.9991 for intra-day and interday, respectively. The method demonstrated a high precision (%RSD values ≤ 5.8%) and accuracy (%RE<9.6%). The LOD and LOQ of gamma-tocotrienol were determined as 1.4 μg/mL and 4.2 μg/mL, respectively. The system suitability studies indicate that the chromatographic parameters are well within the acceptable limit. Conclusion: In conclusion, the developed RP-HPLC method is rapid, precise, stable and economical for the quantification of gamma-tocotrienol.
Keywords: RP-HPLC